Report of the president of the international union Against sexually transmitted infections from November 1999 (38th general assembly, sun city, South Africa) to september 2000 (Executive Committee Meeting, Budapest, Hungary) - Philpot, Ross (Brazilian Journal of Sexually Transmitted Diseases, 2000)
[...]